Infection-associated hemophagocytic syndrome among patients with dengue shock syndrome and invasive aspergillosis: A case series and review of the literature - Noppadol Larbcharoensub (2018)
The authors report four autopsy cases of previously healthy children with dengue shock syndrome complicated with infection-associated hemophagocytosis and invasive aspergillosis. Hemophagocytosis is confirmed by histopathology of autopsied reticuloendothelial organs. All four children were identified to have invasive aspergillosis by histopathology and three cases were positive on fungal culture for Aspergillus spp. Regarding the cause of death among the four children without pre-existing underlying disease, three cases were directly ascribable to invasive aspergillosis and the remaining case was ascribed to dengue shock syndrome. The transmigration of preexisting fungi from the respiratory mucosa damaged by the dengue shock process is postulated as the pathogenesis of invasive aspergillosis. The main predisposing factor was found to be prolonged dengue shock syndrome. We reviewed the clinicopathologic features and therapeutic management of infection-associated hemophagocytic syndrome in patients with dengue shock syndrome and invasive aspergillosis.